ANALISIS DIGITAL CITRA LANDSAT UNTUK DETEKSI PERUBAHAN GARIS PANTAI TRIKORA KABUPATEN BINTAN - Ichsan, Rafiqul M; Jaya, Yales Veva; Putra, Risandi Dwirama; Suhana, Mario Putra (Dinamika Maritim, 2018)
Trikora beach is a coastal area with a diverse set of potential in Bintan. Remote sensing is a technique of detection of an object with a high efficiency level. Information changes the shoreline is required to review the management of the territory. Research on probe coastline changes using Landsat satellite imagery with combine method of Single Band 5 Threshold and Band Ratio the calculate of changes the coastline by Digital Shorline Analysis System. Final results of calculation changes accretion of Trikora coastline caused by the influence of human activity such as infrastructure development and changes of the land function this occurs most obviously seen in the period of the year 1995-2005. The abrasion phenomena for the Trikora Beach caused by natural factors such as wave, changes in the pattern of currents, tidal variations and climate change, this happened during on 1990-1995 years.